2022
DOI: 10.1007/s10973-022-11733-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of heat transfer performance within annular geometries with swirl-inducing fins using clove-treated graphene nanoplatelet colloidal suspension

Abstract: The paper investigated the benefits of having fins that induce swirling flow within an annular passage. The importance of the vortical structures produced using different fin angles and flow velocities in heat transfer was studied. The combination of swirling fluid with recirculation on heat transfer within an annular domain was not fully understood, and this paper aims to address that gap. The 10°, 20°, 30° and 40° angled fins were investigated to understand the changes in heat transfer performance as fluid r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…This indicates that this type of vortex improves heat transfer performance with minimal impact on pressure drop, thus resulting in significantly higher PEC values. This finding expands on the initial finding on longitudinal vortices and their role in improving heat transfer by Nair et al [25], where they found that heat transfer improved when the longitudinal vortex generated by the angled fins was large enough to mix the heated fluid from the thermal boundary layer into the faster-flowing freestream region. In terms of pure improvement to heat transfer, the transverse vortex also appears to contribute meaningfully, as evidenced by the excellent improvement in Nu over the baseline case in Figure 8.…”
Section: Gravitational Impact On Heat Transfer Performancesupporting
confidence: 83%
See 3 more Smart Citations
“…This indicates that this type of vortex improves heat transfer performance with minimal impact on pressure drop, thus resulting in significantly higher PEC values. This finding expands on the initial finding on longitudinal vortices and their role in improving heat transfer by Nair et al [25], where they found that heat transfer improved when the longitudinal vortex generated by the angled fins was large enough to mix the heated fluid from the thermal boundary layer into the faster-flowing freestream region. In terms of pure improvement to heat transfer, the transverse vortex also appears to contribute meaningfully, as evidenced by the excellent improvement in Nu over the baseline case in Figure 8.…”
Section: Gravitational Impact On Heat Transfer Performancesupporting
confidence: 83%
“…This study enhances the initial investigation by Nair et al [25], where angled fins, which encourage swirling flow, were investigated for heat transfer. The swirling nature of the flow when the appropriate fin angles were used, combined with the contribution of the longitudinal and transverse vortices, provided excellent overall improvement in terms of PEC.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Longitudinal vortices rotate perpendicular to the flow direction, whilst transverse vortices rotate parallel to the flow direction. The creation of such vortical structures has shown immense improvements in heat transfer enhancement, due to various ideal flow characteristics induced in the flow [6][7][8][9][10]. In spite of the enhanced heat transfer rates, the presence of fins often leads to increased pressure drop and friction losses across the system, which correlates to higher pumping power requirements [11].…”
Section: Introductionmentioning
confidence: 99%